HEALTH CAMPUS STUDENTS TO SIT FOR EXAM BEGINNING 5 JANUARY 2015 - MPRC, Pusat Media & Perhubungan Awam (USM, 2014)
PENANG, 31 December 2014 Universiti Sains Malaysia (USM) today announced that the students at the Health Campus Kubang Kerian, Kelantan will sit for their semester exam beginning Monday, 5 January to Tuesday, 20 January 2015. The exam originally scheduled to begin on Sunday, 28 December 2014 was postponed due to floods that ravaged Kelantan and several states in the East Coast.